2007
DOI: 10.1111/j.1365-2427.2007.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Stream food web response to a salmon carcass analogue addition in two central Idaho, U.S.A. streams

Abstract: OnlineOpen: This article is available free online at www.blackwell-synergy.com SUMMARY 1. Pacific salmon and steelhead once contributed large amounts of marine-derived carbon, nitrogen and phosphorus to freshwater ecosystems in the Pacific Northwest of the United States of America (California, Oregon, Washington and Idaho). Declines in historically abundant anadromous salmonid populations represent a significant loss of returning nutrients across a large spatial scale. Recently, a manufactured salmon carcass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 40 publications
6
73
0
Order By: Relevance
“…N and P additions in aquatic systems can increase periphyton biomass, chlorophyll accrual rate, and the abundance and biomass of plankton and invertebrate communities (Kohler et al 2008, Kohler andTaki 2010). Investigators also have reported significant increases in salmon production following nutrient addition in nutrient-depleted lakes and streams in British Columbia, Idaho, and Alaska (Johnson et al 1990, Stockner 2003.…”
mentioning
confidence: 99%
“…N and P additions in aquatic systems can increase periphyton biomass, chlorophyll accrual rate, and the abundance and biomass of plankton and invertebrate communities (Kohler et al 2008, Kohler andTaki 2010). Investigators also have reported significant increases in salmon production following nutrient addition in nutrient-depleted lakes and streams in British Columbia, Idaho, and Alaska (Johnson et al 1990, Stockner 2003.…”
mentioning
confidence: 99%
“…Condition, production, and lipid concentrations of stream-resident cutthroat trout (Oncorhynchus clarki) and production and lipid content of young-of-theyear coho salmon (Oncorhynchus kisutch) increased in natural and artificial stream channels following SCA treatment . Kohler et al (2008) demonstrated a positive stream foodweb response to SCA additions. The responses included elevated periphyton chlorophyll a and ash-free dry mass (AFDM), macroinvertebrate density and biomass, periphyton and macroinvertebrate stable isotope (d 15 N) values, and increased leaf decomposition rates in a stream reach containing SCA.…”
mentioning
confidence: 99%
“…Kohler et al (2008) demonstrated gross stream foodweb responses to SCA treatment, but ecologically meaningful effects on macroinvertebrate assemblages might have gone undetected. Macroinvertebrate communities represent a potentially important vector of marine-derived nutrients to aquatic and terrestrial consumers and warrant closer examination.…”
mentioning
confidence: 99%
See 2 more Smart Citations